2021
DOI: 10.3390/agronomy11081607
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Plant Assisted Synthesis of Cobalt Oxide Nanoparticles and Their Antimicrobial Activities

Abstract: The development of sustainable, ecofriendly, and cost-effective methods for the synthesis of nanomaterials is an important aspect of nanotechnology these days. The present study was aimed at synthesizing cobalt oxide (Co3O4) nanoparticles by using plant extracts of Aerva javanica, bacterial isolates from rhizospheric soil of Potentilla atrosanguinea, Swertia petiolata, Senecio chrysanthemoides, and from fungus Fusarium oxysporum. X-ray diffraction spectroscopy (XRD) and scanning electron microscopy (SEM) techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Cobalt nanoparticles have many applications in catalysis, energy storage, as contrast agents in biomedicine, in waste water treatment, and as antimicrobial and anticancer agents [17,3]. Several studies have used plant extracts and bacteria to synthesise cobalt nanoparticles, but in all these studies, the use of high temperature from 80 °C to 850 °C and/or other reagents [18, 19, 20, 21, 22] was required to synthesise the nanoparticles. Thus, our study demonstrates an ecofriendly and sustainable approach to nanoparticle synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Cobalt nanoparticles have many applications in catalysis, energy storage, as contrast agents in biomedicine, in waste water treatment, and as antimicrobial and anticancer agents [17,3]. Several studies have used plant extracts and bacteria to synthesise cobalt nanoparticles, but in all these studies, the use of high temperature from 80 °C to 850 °C and/or other reagents [18, 19, 20, 21, 22] was required to synthesise the nanoparticles. Thus, our study demonstrates an ecofriendly and sustainable approach to nanoparticle synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The desperate attempts require to identify novel antimicrobial agents or developing new procedures to thwart antibiotic resistance (Abdalla et al, 2020 ; Kapadia et al, 2021 ). The advanced and innovative antimicrobial agents developed so far target only the most prominent pathogenic bacteria (Dellit et al, 2007 ), while less severe pathogenic bacteria remain resistant (Masood et al, 2021 ; Mubraiz et al, 2021 ). Therefore, developing innovative strategies which target pathogenesis-responsible compounds are of prime importance for controlling pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of Cu and CoNPs was performed using ultraviolet-visible spectroscopy (UV-vis; UV-1700, Shimadzu) and Fourier-transform infrared spectroscopy (FTIR; Bruker Alpha Platinum ATR) . For UV-vis spectroscopy, Co and CuNPs solutions were used by absorbing light emitted by substances, thus showing the UV-visible absorption spectrum of Co and CuNPs 14) . FTIR study was performed using the dry powder form of prepared NPs and showed different functional groups present in the Co and CuNPs 12) .…”
Section: Characterization Of Co and Cunpsmentioning
confidence: 99%
“…High surface-to-volume ratios and nano scale sizes are distinguishing characteristics of biogenic NPs, which improve their reaction with pathogenic microbes. 1) 14,15) . E. coli and B. subtilis CuNPs showed higher ZOI against Gram-negative (E. coli) than Gram-positive strain (B. subtilis) .…”
Section: Antibacterial Assay Of Co and Cunpsmentioning
confidence: 99%